T3 is linked to stress‐associated reduction of prolactin in lactating women. (9th July 2021) - Bibi, Safia; Shah, Mohsin; Malik, Muhammad Omar; Goosens, Ki Ann
Abstract: The relationship between stress responses and lactation is bidirectional. Breastfeeding confers many benefits to maternal health, including attenuated hypothalamic‐pituitary‐adrenal axis responsiveness to stress. However, increased stress burden can impair lactation. The mechanisms that underlie these relationships are poorly understood. The present study aimed to compare breastfeeding habits, as well as subjective and objective measures of stress, in employed and non‐employed lactating women and assess the relationships between these measures and prolactin (PRL), thyroid hormones (thyroid‐stimulating hormone, triiodothyronine [T3] and thyroxine), vasopressin and cortisol levels. A dexamethasone suppression test was also administered to determine the sensitivity of the hypothalamic‐pituitary‐adrenal axis to negative‐feedback. We report that lactating employed women had lower breastfeeding rates and lower PRL than lactating non‐employed women. They also had a significantly higher stress burden, indicated by elevations in blood pressure and evening cortisol, relative to lactating non‐employed women. In regression analyses that controlled for feeding modality and breastfeeding duration, we found these factors differentially affected PRL in the two groups and there were significant differences in PRL across groups that were not accounted for by these factors. A mediation regression analysis suggested that group differences in PRL were best explained by differences in T3 and income levels, rather than breastfeeding duration or other variables. Our data fit a speculative model in which elevated maternal stress increases cortisol, which suppresses T3, leading to decreased PRL. The decreases in PRL are associated with higher rates of bottlefeeding, which may further contribute to decreased PRL. Abstract : Workplace stress exposure is associated with hypothalamic‐pituitary‐adrenal axis activation, which is associated with decreased triiodothyronine within the thyroid gland. The decrease in triiodothyronine is linked to prolactin levels in employed mothers.